Financing indigenous entrepreneurs: a review and research agenda - De Gruyter, E; Gordon, J; Qureshi, I; Bhatt, B; Mafico, N (SAGE Publications, 2024)
Empowering Indigenous communities through entrepreneurialism is touted as key for reducing Indigenous disadvantage, but little headway has been made. One core and persistent issue is difficulty accessing finance to support growth. To understand why and to guide future policy and research, we review the current state of research on Indigenous financing and develop a thematic framework around four themes: political-economic environment; antecedents to the financing decision; financial solutions; and financial preferences, decisions and outcomes. Indigenous entrepreneurs face unique intercultural, social and economic barriers to finance, and these need to be better understood to help accelerate Indigenous community development through entrepreneurial activity.